Disaster consequence mitigation and evaluation of roadside green spaces in Nanjing - Fei, Wenjun; Jin, Zhijia; Ye, Jienan; Divigalpitiya, Prasanna; Sakai, Takeru; Wang, Chengkang (Journal of Environmental Engineering and Landscape Management, 2019)
The extensive layout of roadside green spaces make them important green disaster mitigation nodes in high-density areas of any city; hence, further improvements in their disaster mitigation functions would make the urban disaster prevention system more effective. In the present research, different types of roadside green spaces in the Gulou district of Nanjing were identified to establish a highly efficient urban disaster refuge green space system. A total of 35 built-up roadside green spaces were employed as the study site, and for field investigation and statistical analysis, 21 factors were selected from the aspects of spatial form, functional facilities, and surrounding environment. According to their disaster mitigation abilities, cluster analysis classified these roadside green spaces into four categories: complete type, potential type, centralized type, and broad type. Finally, by analyzing the characteristics of different types of roadside green spaces, corresponding optimization strategies were proposed. In comparison to previous investigations, our study focused on the quantitative evaluation of disaster mitigation and risk protection function of roadside green spaces. In the future, the obtained results will serve as important scientific references to the planning and construction of green spaces in high-density areas of Nanjing, China.